2015
DOI: 10.1111/lcrp.12087
|View full text |Cite
|
Sign up to set email alerts
|

Observing offenders: Incident reports by surveillance detectives, uniformed police, and civilians

Abstract: Purpose Police officers often write reports about witnessed incidents, which may serve as evidence in court. We examined whether incident reports and identifications by police officers, and in particular specialized detectives on surveillance teams, are more complete or more accurate than reports and identifications by civilian observers. Methods Our sample included 46 civilians, 52 uniformed police officers, and 42 surveillance detectives. Participants viewed a 15‐min video of a drug transaction and were allo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…When police officers provide written or oral incident reports, they can often rely not only on their memory of what happened, but also on external aids such as notes that they took at the crime scene or during real-time observations (e.g., perpetrator descriptions or details about the vehicle). Yet, to our knowledge, only two studies to date have assessed this combination of observation and memory (one of which was unpublished; Marshall & Hanssen, 1974, as cited in Ainsworth, 1981; and the other one recently published; Vredeveldt, Knol, & Van Koppen, 2015). In both studies, it was found that police officers reported more correct information about the witnessed event than civilians.…”
Section: Observation and Recall Of Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…When police officers provide written or oral incident reports, they can often rely not only on their memory of what happened, but also on external aids such as notes that they took at the crime scene or during real-time observations (e.g., perpetrator descriptions or details about the vehicle). Yet, to our knowledge, only two studies to date have assessed this combination of observation and memory (one of which was unpublished; Marshall & Hanssen, 1974, as cited in Ainsworth, 1981; and the other one recently published; Vredeveldt, Knol, & Van Koppen, 2015). In both studies, it was found that police officers reported more correct information about the witnessed event than civilians.…”
Section: Observation and Recall Of Eventsmentioning
confidence: 99%
“…Beyond overall differences in reporting about witnessed incidents, perhaps a more interesting finding is that police officers report more crime-relevant information, for example about perpetrators, weapons, and vehicles, but not more crime-irrelevant information, for example about victims, bystanders, and contextual setting (Kalteis, 2013; Kaminski & Sporer, 2016; Lindholm et al, 1997; Smart et al, 2014; Vredeveldt, Knol, et al 2015). It seems likely that this difference occurs already at the encoding stage of memory; that is, police officers pay attention to different things than civilians do.…”
Section: Observation and Recall Of Eventsmentioning
confidence: 99%
“…Observation is crucial to certain aspects of law enforcement work and investigation. Exploring the impact of expertise on incident report-writing skills, Vredeveldt, Knol, and van Koppen (2017) found that surveillance detectives provided more accurate incident reports that may serve as evidence in court than both untrained civilians and uniformed police officers, suggesting that specialized detectives on surveillance teams are more observant of the crime-relevant aspects of an incident. In a related surveillance task, Stainer, Scott-Brown, and Tatler (2013) found that trained CCTV operators spent most of their time searching on the single-scene spot-monitor, rather than spending a lot of time viewing the multiplex wall, suggesting a selective approach based on crime likelihood prediction.…”
Section: Visual Perception and Observation Skillsmentioning
confidence: 99%
“…However, Maccoby and Jacklin (1974) claimed that stable gender-related differences do not exist in most laboratory conditions. Nevertheless, some of the research that followed (e.g., Horgan et al, 2004;Rehnman & Herlitz, 2007;Areh, 2011;Vredeveldt et al 2015;Longstaff & Belz, 2020) also found gender effects in whole or in part.…”
Section: Introductionmentioning
confidence: 99%
“…To complicate matters further, Deblieck & Zaidel (2003) found that females were better at remembering attractive faces both male and female), but that males were better at remembering unattractive faces (of both genders). However, other researchers have found female superiority regarding face recognition regardless of target gender, especially when asked to describe others' appearance (Horgan et al, 2004, Areh, 2011Vredeveldt et al, 2015). Even more complicating is that some authors have found that female witnesses perform better only when recognising female faces (e.g., Lewin The authors who have found a female superiority have provided different explanations.…”
Section: Introductionmentioning
confidence: 99%